Identifikasi Kerusakan Dini Otomatis Komponen Elektronika Berbasis Arus Dengan Mikrokontrol Arduino Uno - Agus Rianto; Jani Kusanti (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
Electric current is the flow of electricity in an electronic circuit where the amount flows through the circuit. The greater the current flowing in the circuit, the greater the value in amperes. The components in electronic circuits always have an electric current flowing through them. The electric current in this component is the basis for knowing whether the component is in good condition or not. On this basis, researchers use current sensors to detect damage to electronic components. In designing DC Current Based Early Damage Identification of Electronic Components with Text Notifications on the LCD using the Arduino UNO microcontroller, the current sensor is used, namely the ACS 712 current sensor. This Electronic Component Early Damage Identification Tool works automatically, the system will provide automatic error information via notifications on the LCD and the system will stop itself if one of the components is damaged. With this tool, Early Damage Identification of Electronic Components Based on DC Current with Text Notification on the LCD using the Arduino UNO microcontroller will make repairs easier and faster if one of the components is damaged. Because the notification on the LCD will notify you of damage to the damaged component